Correction to: Somatic symptom and related disorders in children and adolescents: Evaluation of a naturalistic inpatient multidisciplinary treatment (Child and Adolescent Psychiatry and Mental Health (2018) 12 (34) DOI: 10.1186/s13034-018-0239-y) - Heimann, P (2020)
10.1186/s13034-018-0253-0